2019
DOI: 10.1101/715326
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A dynamic role for dopamine receptors in the control of mammalian spinal networks

Abstract: Dopamine is well known to regulate movement through the differential control of direct and indirect pathways in the striatum that express D1 and D2 receptors respectively. The spinal cord also expresses all dopamine receptors however; how the specific receptors regulate spinal network output in mammals is poorly understood. We explore the receptor-specific mechanisms that underlie dopaminergic control of spinal network output of neonatal mice during changes in spinal network excitability. During spontaneous ac… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 79 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…This preparation also allowed us to manipulate and assess the relative contribution of certain currents, which the model predicts play a key role in the rhythmic network activity. Similar forms of episodic rhythmicity are not exclusive to dopamine application (Sharples and Whelan 2017; Sharples et al 2020); they can be evoked by trace amines (Gozal et al 2014) and activation of excitatory tachykinin receptors (Barbieri and Nistri 2001; Marchetti and Nistri 2001) in neonatal mouse and rat spinal cord. Further, episodic rhythms generated in vitro display consistent temporal properties to swim episodes in mature zebrafish (Müller, Stamhuis, and Videler 2000; Gabriel et al 2011; Currie et al 2016) and juvenile (P11-15) mouse isolated spinal preparations (Mahrous and Elbasiouny 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This preparation also allowed us to manipulate and assess the relative contribution of certain currents, which the model predicts play a key role in the rhythmic network activity. Similar forms of episodic rhythmicity are not exclusive to dopamine application (Sharples and Whelan 2017; Sharples et al 2020); they can be evoked by trace amines (Gozal et al 2014) and activation of excitatory tachykinin receptors (Barbieri and Nistri 2001; Marchetti and Nistri 2001) in neonatal mouse and rat spinal cord. Further, episodic rhythms generated in vitro display consistent temporal properties to swim episodes in mature zebrafish (Müller, Stamhuis, and Videler 2000; Gabriel et al 2011; Currie et al 2016) and juvenile (P11-15) mouse isolated spinal preparations (Mahrous and Elbasiouny 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Notably, I h plays an important role in controlling the ED, which is supported by both our model and experimental results, and also episode stability which is consistent with our previous work demonstrating a prominent role for dopamine in reducing variability in the cycle period in locomotor-like rhythms (Sharples et al 2015). The bidirectional receptor-dependent modulatory effects of dopamine (Sharples et al 2020) could be mediated by adjusting the balance of the I Pump (Picton et al 2017) and I h in spinal neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, increasing evidence suggests that DA might also indirectly control locomotion through A9/A10 and A13 descending DA pathways which innervate the two major brainstem excitatory nuclei of mesencephalic locomotor region, the pedunculopontine nucleus and the cuneiform nucleus (Ryczko et al, 2016;Ryczko and Dubuc, 2017;Sharma et al, 2018). Finally, recent works indicate that opto-activation of the descending DA pathway originating from A11 nuclei known to modulate spinal networks involved in the control of rhythmic movements (Han et al, 2007;Pappas et al, 2008;Sharples et al, 2020;Sharples et al, 2014) is sufficient to increase both locomotion and in-place activity (Koblinger et al, 2018). Surprisingly, no evidence has yet indicated that this pathway might participate in the regulation of motor behaviors induced by psychostimulants.…”
Section: Discussionmentioning
confidence: 99%
“…These data are closely consistent with the idea that modulators contribute to setting the state of excitability and the mode of operation of the spinal locomotor networks (Sharples & Whelan, 2017), notably allowing switches from intermittent to continuous episodes of locomotion, and conversely (Sharples et al . 2020). Dopaminergic and most 5‐HT receptors mediate their cellular action through a modulation of adenylate cyclase (AC) and the production of cyclic AMP (for review, Missale et al .…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that the basal levels of monoamines that we observed in the absence of pharmacological stimulation were in a range similar to that reported in the neonatal mouse spinal cord (Sharples et al . 2020). However, we do not rule out contribution of the serotonergic and noradrenergic signalling in the pro‐locomotor effect of L‐DOPA.…”
Section: Discussionmentioning
confidence: 99%